Synthesizing sustainable construction paradigms: A comprehensive review and bibliometric analysis of granite waste powder utilization and moisture correction in concrete - Raman Sphurty; Nateriya Raman (Reviews on Advanced Materials Science)
This comprehensive review and scientometric analysis address the critical need for sustainable construction practices by examining the utilization of granite waste in concrete. The study responds to mounting environmental challenges in construction waste management, particularly addressing granite processing waste which comprises 50–60% of production [Indian Bureau of Mines. ariMinerals yearbook 2021 (Part-III: Mineral reviews), 60th edn, Granite (Advance Release), Indian Bureau of Mines, Ministry of Mines, Government of India, Nagpur, 2021.]. Through rigorous analysis of 585 publications from 2008 to 2024, the study reveals optimal granite waste replacement levels of 20–25% for sand and 10–15% for cement, yielding enhanced mechanical properties with compressive strengths up to 66 and 72 MPa, respectively. The research emphasizes the crucial role of moisture correction based on saturated surface dry conditions for consistent performance. Key findings demonstrate that granite waste can effectively replace up to 25% of sand and 15% of cement, contributing to reduced landfill use and lower CO2 emissions. The study identifies research gaps, including limited long-term durability studies and the need for standardization. Future directions propose investigating synergies with other supplementary cementitious materials and applications in emerging concrete technologies. This work provides a framework for optimizing granite waste in concrete, balancing environmental benefits with improved mechanical properties, and offering valuable insights for developing sustainable concrete solutions that potentially reduce environmental impact while enhancing performance.